Fracture resistance of endodontically-treated teeth submitted to bleaching treatment with hydrogen peroxide and titanium dioxide nanoparticles photoactivated by LED-laser - Jordão-Basso, Keren Cristina [UNESP]; Andolfatto, Carolina [UNESP]; Kuga, Milton Carlos [UNESP]; Chávez-Andrade, Gisselle Moraima [UNESP]; Faria-Júnior, Norberto Batista de [UNESP]; Faria, Gisele [UNESP]; Madeira-Neto, Paulo [UNESP]; Oliveira-Junior, Osmir Batista de [UNESP] (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
Objective:The aim of this study was evaluate the fracture resistance of endodontically-treated teeth after bleaching treatment using 15% hydrogen peroxide plus titanium dioxide nanoparticles (15HPTiO2) photoactivated by LED-laser, in comparison with protocols using 35% hydrogen peroxide (35HP), 37% carbamide peroxide (37CP) or sodium perborate (SP).Material and method:After endodontic treatment, fifty bovine extracted incisors were divided into five groups (n = 10): G1- without bleaching; G2- 35HP; G3- 37CP; G4- 15HPTiO2 photoactivated by LED-laser and G5- SP. In G2 and G4, the bleaching protocol was applied in 4 sessions, with a 7 day interval between each session. In G3 and G5, the materials were kept in the pulp chamber for 21 days, but replaced every 7 days. After 21 days, the crowns were subjected to compressive load at a cross head speed of 0.5 mm/min, applied at 135° to the long axis of the root using an eletromechanical testing machine, until fracture. The data were submitted to ANOVA and Tukey tests (p = 0.05).Result:The bleaching treatment in endodontically-treated teeth with 15HP plus TiO2 nanoparticles and photoactivated by LED-laser caused reduction of the fracture resistance similarly provided by 35HP, 37CP or SP (p>0.05). All bleaching treatments reduced the fracture resistance compared to unbleached teeth (p<0.05).Conclusion:All bleaching protocols reduced the fracture resistance of endodontically-treated teeth, but there were no differences between each other.

Objetivo:Avaliar a resistência à fratura de dentes tratados endodonticamente após tratamento clareador usando peroxido de hidrogênio a 15% com nanopartículas de dióxido de titânio (15HPTiO2) fotoativado por LED-laser, em comparação aos protocolos usando peróxido de hidrogênio 35% (35HP), peróxido de carbamida 37% (37CP) ou perborato de sódio (SP).Material e método:Após tratamento endodôntico, 50 incisivos bovinos extraídos foram divididos em 5 grupos (n = 10): G1- sem clareamento; G2- 35HP; G3- 37CP; G4- 15HPTiO2 fotoativado por LED-laser e G5- SP. Nos grupos G2 e G4, o protocolo de clareamento foi aplicado em 4 sessões, com 7 dias de intervalo entre cada sessão. Nos grupos G3 e G5, os materiais foram inseridos na câmara pulpar por 21 dias e trocados a cada 7 dias. Após 21 dias, as coroas foram submetidas à força de compressão com velocidade de 0,5 mm/min, aplicada a 135º em relação ao longo eixo da raiz. empregando máquina de ensaios mecânicos, até a fratura. Os dados foram submetidos aos testes de ANOVA e Tukey (p = 0.05).Resultado:O tratamento clareador em dentes tratados endodonticamente com 15HP e nanopartículas de TiO2 fotoativado por LED-laser proporcionou redução da resistência à fratura semelhante ao 35HP, 37CP ou SP (p>0,05). Todos os tratamentos clareadores reduziram a resistência coronária à fratura quando comparados aos dentes sem tratamento (p<0,05).Conclusão:Todos os protocolos de clareamento reduziram a resistência à fratura dos dentes tratados endodonticamente, sem diferenças estatisticamente significantes entre os grupos.
Resistência à fratura de dentes tratados endodonticamente submetidos a tratamento clareador com peróxido de hidrogênio e nanopartículas de dióxido de titânio fotoativado por LED-laser
Keywords: Nanoparticles; peroxides; tooth bleaching; Nanopartículas; peróxidos; clareamento dental